Quantitative dynamic 18F-fluorodeoxyglucose positron emission tomography/computed tomography before autologous stem cell transplantation predicts survival in multiple myeloma: letters to the editor - Sachpekidis, Christos; Merz, Maximilian; Kopp-Schneider, Annette; Jauch, Anna; Raab, Marc-Steffen; Sauer, Sandra; Hillengaß, Jens; Goldschmidt, Hartmut; Dimitrakopoulou-Strauss, Antonia (Haematologica, 2019)
Although the presence of focal lesions in 18F-fluo-rodeoxygluocse (FDG) positron emission tomography (PET)/computed tomography (CT) is associated with adverse outcome in multiple myeloma, data on diffuse bone marrow infiltration are lacking. In the current prospective study we investigated the